Meningkatkan Kemampuan Berpikir Kritis Dengan Menggunakan Model Problem Based Learning Materi Manusia Makhluk Otonom Pada Kelas X-1 SMA Marsudirini Bogor - Anastasia Purwanti (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Education is one of the main foundations of a nation's development. Through education, young individuals are prepared to face the challenges of the future, developing the skills, knowledge, and values needed to contribute to the development of society and the country. A religious teacher has dual duties and roles as a preacher and educator. Realizing the tasks that exist within a religious teacher, researchers want to improve the ability of one aspect of students, namely critical thinking. The more often students are trained to think critically during the learning process in class, the more students' knowledge and experience will increase in solving problems inside and outside the classroom. Based on the results of initial observations carried out by researchers in class This can be shown from the number of students who dare to ask questions. Of the 17 students, only 3 people actively asked questions during the learning process. Apart from that, the questions asked by students are still at the memory level and the answers can be obtained from the textbook. Students are also not able to make learning conclusions in their language. Based on the problems above, the author believes that the Problem-Based Learning (PBL) learning model can improve students' critical thinking skills and also strengthen the value of the Pancasila student profile. This research aims to describe the influence of the Problem-Based Learning learning model on critical thinking skills regarding Autonomous Human Beings in class X-1 students at Marsudirini Bogor High School. The type of research used is qualitative with a descriptive approach. Data collection techniques in this research used observation and written tests. The data analysis technique used consists of data reduction by selecting raw data into information, presenting data in the form of descriptions, tables, and graphs, as well as drawing conclusions using conclusions from research results that refer to the problem formulation. The use of the Problem-Based Learning model according to the syntax which includes orienting students to problems, organizing students to learn, guiding individual or group investigations, developing and presenting results, analyzing and evaluating the problem-solving process, is effective in improving critical thinking skills and participant learning outcomes educated on the subject of Human Autonomous Creatures in class X-1 of Marsudirini Bogor High School.